2017
DOI: 10.1002/eji.201747174
|View full text |Cite
|
Sign up to set email alerts
|

TCR‐pMHC encounter differentially regulates transcriptomes of tissue‐resident CD8 T cells

Abstract: To investigate the role of TCR-pMHC interaction in regulating lung CD8 tissue-resident T cell (T ) differentiation, polyclonal responses were compared against NP /D and PA /D , two immunodominant epitopes that arise during influenza A infection in mice. Memory niches distinct from iBALTs develop within the lamina propria, supporting CD103 and CD103 CD8 T generation and intraepithelial translocation. Gene set enrichment analysis (GSEA) and weighted gene co-expression network analysis (WGCNA) identify dominant T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 99 publications
(125 reference statements)
1
37
0
Order By: Relevance
“…Lung Trm, similar to Trm characterized in other tissues, are a self-sustaining population that are maintained with minimal need for replenishment by the circulating memory T cell pool (19,20,(95)(96)(97). In the lung, CD4 + and CD8 + Trm congregate either within or around inducible bronchial-associated lymphoid tissue, respectively, and are also enriched in areas where the lung tissue has been remodeled postinfectionassociated injury (19,98,99). Trm express a variety of adhesion molecules and proteins that facilitate their longterm retention and survival in the lung (19) (Fig.…”
Section: Development Of Iav-specific Memory T Cell Responsesmentioning
confidence: 98%
See 2 more Smart Citations
“…Lung Trm, similar to Trm characterized in other tissues, are a self-sustaining population that are maintained with minimal need for replenishment by the circulating memory T cell pool (19,20,(95)(96)(97). In the lung, CD4 + and CD8 + Trm congregate either within or around inducible bronchial-associated lymphoid tissue, respectively, and are also enriched in areas where the lung tissue has been remodeled postinfectionassociated injury (19,98,99). Trm express a variety of adhesion molecules and proteins that facilitate their longterm retention and survival in the lung (19) (Fig.…”
Section: Development Of Iav-specific Memory T Cell Responsesmentioning
confidence: 98%
“…Studies in animal models have defined key developmental requirements of lung Trm and identified factors within the lung microenvironment that promote Trm differentiation and maintenance. Optimal development of influenza virus-specific CD8 + Trm in the lung requires the following: 1) local cognate Ag recognition in the tissue (15,20,110), 2) exposure to locally produced TGF-b (99,102,103), and 3) the presence of IFN-g-secreting CD4 + T cells (111) (Fig. 1).…”
Section: Development Of Iav-specific Memory T Cell Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…67,72,73 Further, TCR signal can induce the expression of anti-viral protein IFITM3 (Interferon Induced Transmembrane Protein 3) in lung T RM cells. IFITM3 protects lung T RM cells from direct viral infection-induced cell death.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…These lung T RM niches are the tissue repair-associated regions and co-localize with the production of T RM promoting factors TGF-β and IL-15. 47,72 Notably, the regeneration of damaged airway epithelium is also TGF-β-dependent, 78 providing an example of complex functions of TGF-β signaling in both local immunity and tissue homeostasis. The gradual decline of lung T RM cells is caused by the completion of injured lung regeneration and the shrinking of lung T RM niches.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%